PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE INSTANT ASSESSMENT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 4 PAINAN TAHUN PELAJARAN 2013/2014 - Rahma Delta, Aflariza; Longgom Nasution, Minora; Lovia, Lita (Pendidikan Matematika, 2014)
ABSTRACTThe problem of this research is the students have lack to respond the material and less confident. The purpose this research is to find out how the studentsâ activity in learning mathematic and are the studentsâ comprehension in mathematic concept by applying instant assessment is better than conventional learning. This is an experimental research. The population is students at grade seventh at SMPN 4 Painan. The sample is students VII.1 as experimental class and students VII.2 as control class. The instrument is questionnaire and essay form with reliability is 0,986.An average at experiment class is 77,74 with standard deviation is 8,39 meanwhile control class is 72,73 with standard deviation is 11,17.hypothesis test used t-test one side. An analysis of data thitung is 1,85 and ttable is 1,68. The hypothesis can be accepted. The conclusion is the studentsâ comprehension in mathematic concept by applying instant assessment is better than conventional learning.